Effects of correct and wrong answers on ERPs recorded under conditions of the continuous performance test in ADHD/normal participants - Ghassemi, F.; Moradi, M.H.; Tehrani-Doost, M.; Abootalebi, V. (Нейрофизиология, 2010)
Parameters of event-related potentials (ERPs) regarding correct and wrong answers under conditions of the continuous performance test (CPT) were measured in 50 adult subjects with the absence/presence of attention deficit/hyperactivity disorders (ADHD) and characterized by different levels of sustained attention. For ERP extraction, the average for each group of signals, which were time-locked to the onset of stimuli, was calculated; two ERP groups were considered separately for correct and wrong answers. In both groups, the P300 wave was clearly observed. The time dynamics of ERP components were investigated in six defined time blocks. At the peak of P300, a prominent component of brain activity could be observed. Some ERP morphological features (704 items) were extracted from these potentials. The results indicated that 11 of the obtained features had a significant (P<0.01) relation to the level of sustained attention. When comparing correct and wrong answers, 10 features in the normal group and 3 features in the ADHD group demonstrated significant differences (P < 0.05), which means that the participant’s response is reflected in the features of EEG signal. The results reveal a promising relation between CPT results and some parameters of brain signals, which can be used for further evaluations of the sustained attention level. Параметри пов’язаних з подією ЕЕГ-потенціалів (ППП) вимірювали у 50 дорослих тестованих з відсутністю (норма) та наявністю синдрому дефіциту уваги й гіперактивності (АDНD), котрі демонстрували різні градації рівня підтримуваної уваги. Враховували правильність і помилковість відповідей в умовах тесту безперервного виконання (continuous performance test, CPT). Щоб описати ППП, розраховували середні значення для кожної групи сигналів, «прив’язаних» до моменту пред’явлення стимулу. Було виділено дві окремі групи ППП, відповідно до вірних та помилкових відповідей. Хвиля Р300 була чітко представлена в обох групах ППП. Часова динаміка компонентів ППП була досліджена в межах шести ізольованих часових блоків. Пік Р300 віддзеркалював чітко виражений компонент церебральної активності. У складі ППП було виділено низку морфологічних особливостей (усього 704 риси). Виявилося, що 11 з таких рис вірогідно (P < 0.01) корелювали з рівнем постійної уваги. При порівнянні ППП, пов’язаних з вірними та хибними відповідями, істотні відмінності демонстрували 10 рис у групі норми та три риси в групі АDНD (P < 0.05). Це свідчить про те, що характер відповіді тестованого певним чином віддзеркалюється в патерні ЕЕГ-сигналу. Отримані дані вказують на наявність зв’язку між результатами СРТ і деякими параметрами ЕЕГ-сигналів. Це може бути використано для об’єктивної оцінки рівня підтримуваної уваги.